Comprehensive genetic analysis of histological components of combined small cell carcinoma. Issue 16 (11th July 2022) - Iida, Yuko; Nakanishi, Yoko; Shimizu, Tetsuo; Nomoto, Masayuki; Nakagawa, Yoshiko; Ito, Reiko; Takahashi, Noriaki; Masuda, Shinobu; Gon, Yasuhiro
Abstract: Background: Combined small‐cell lung cancer (cSCLC) is a rare type of small‐cell lung cancer (SCLC) that includes both SCLC and non‐small‐cell lung cancer (NSCLC). The molecular biological mechanisms underlying the heterogeneity of histological types in combined or metachronously transformed SCLC (mtSCLC) remain unclear. This study aimed to investigate the relationship between genetic alterations and each histological component heterogeneously detected in cSCLC and mtSCLC. Methods: This study included four cSCLC cases and one mtSCLC case. Formalin‐fixed and paraffin‐embedded sections of each histological component of these tumors were subjected to next‐generation sequencing (NGS) and quantitative reverse transcription‐polymerase chain reaction to investigate the genetic mutations and expression levels of neuroendocrine cell‐specific transcription factors (achaete‐scute homolog‐1 [ASCL1], brain‐2 [BRN2] also known as POU domain class 3 transcription factor 2, nuclear factor 1 B [NF1B], insulinoma‐associated protein 1 [INSM1], and thyroid transcription factor‐1 [TTF‐1]). Results: NGS analysis revealed that SCLC and NSCLC components share the same somatic mutations detected most frequently in TP53, and also in RB1 and EGFR . Gene expression analysis showed ASCL1 expression was significantly lower in the NSCLC component than in the SCLC component. Conclusion: We conclude that the morphological evolution of heterogeneous histological components in cSCLC may be associated with differences in ASCL1 expression levels, but not in acquired somatic gene mutations. Abstract : We investigated the relationship between genetic alterations and each histological component heterogeneously detected in combined SCLC (cSCLC) and metachronously transformed SCLC. The different histological components of cSCLC shared the same major somatic mutations, but ASCL1 expression was lower in the NSCLC component than in the SCLC component. Each histological component of cSCLC undergoes morphological evolution depending on the difference in ASCL1 expression, not due to the differences in acquired somatic mutations.